IMPLEMENTATION OF THE COMBINATION OF EXPLICIT INSTRUCTION MODEL, DRILL METHOD AND MEDIA BOWLING IN DEVELOPMENT MOTOR ROUGH AT GROUP A KINDERGARTEN - Muhammad Galih Asyari; Deasy Arisanty (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
The problem of this research is the low on motor rough in using the right hand and left hand in throwing in a directional manner. This is because the child has not been able to show the attitude of throwing on target, the presentation of learning activities carried out by the teacher is less attractive. The research method used is a literature study by collecting articles related to the research. The effort to improve activities and learning outcomes through explicit instruction model learning methods, drill methods and bowling media. The purpose of this study was to determine the teacher's activity steps, children's activities and the result of children's development in the ability to throw directed at group A children. It can be concluded that using an explicit instruction model, drill method and bowling media through directed throwing activities using the right and left hand can develop teacher and children's activities, and develop children's motor rough skills in group A Kindergarten.